Trade Unions and Wage Inflation in the United Kingdom 1893-1961 - Hines, A. G. (Review of Economic Studies, 1964)
Trade Unions and Wage Inflation in the United Kingdom 1893–1961 Get access A. G. Hines A. G. Hines London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 31, Issue 4, October 1964, Pages 221–252, https://doi.org/10.2307/2295897 Published: 01 October 1964